Vedibandha (basal mouldings) of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the vedibandha (basal mouldings) of the Chaunsath Yogini Temple that are made up of a graaspatti (band of kirtimukhas or face of glory), gajathara (a band of elephants), narathara (a band of human figures), narathara, kumbha (pot) moulding, kalasaha (a pitcher) and kapotali (cyma recta). The most ornate moulding in the entire plinth is the kumbha, which has one central deity, usually a depiction of a goddess, flanked by mithuna (amorous couples) figures or ascetics.